Studies on Chalcones: Part-1â‰ . By green process and evaluation of biological activity - Patil, C. J. (International Journal of Pharmaceutical & Biological Archive, 2017)
Chalcones were prepared by condensation (Claisen Schmidt) reaction of Acetophenone, o-Hydroxyacetophenonewith Benzaldehyde, employing conventional and microwave assisted-solvent free method.This reaction was carried out with use of fresh anhydrous Na2CO3 as catalyst by avoiding hazardousbases like NaOH and KOH for the condensation process which is ecofriendly and covers Green chemistryaspects. Their biological Activities were also evaluated.